COVID19 detection in appendix of acute appendicitis in a child: a case report and review of literature - Jun Kono; Koichiro Yoshimaru; Toshiharu Matsuura; Akihiko Tamaki; Junkichi Takemoto; Shinya Matsumoto; Taeko Hotta; Kenichi Kohashi; Yoshinao Oda; Tatsuro Tajiri (Surgical Case Reports)
Abstract Background Gastrointestinal symptoms are one of the most common presentations of Coronavirus disease-19 (COVID-19), even in children. Higher rates of complicated appendicitis have been demonstrated in the era of the COVID-19 outbreak, and it has been recently suggested that acute appendicitis may occur as a complication of COVID-19. However, the relationship between appendicitis and COVID-19 remains unclear. Case presentation A 7-year-old male presented to the pediatric emergency department with 2 days’ history of lower abdominal discomfort and tenderness. On examination, his abdomen was distended with diffuse mild tenderness at the lower abdomen, which was aggravated by movement. He was also tested and was found to be positive for SARS-CoV-2. Computed tomography showed perforated appendicitis with a fecalith. The patient was admitted and laparoscopic appendectomy was successfully performed. Postoperatively, a minor intra-abdominal abscess was present, which successfully treated with antibiotics. Histopathology showed a markedly inflamed appendix with mucosal ulceration and transmural neutrophilic inflammation, which was consistent with phlegmonous appendicitis. Reverse transcription quantitative polymerase chain reaction using a surgically extracted appendix specimen revealed the presence of SARS-CoV-2 virus, which indicated a pathophysiological relationship between appendicitis and COVID-19. Conclusion The present case will provide further understanding of pediatric patients with concomitant COVID-19 and acute appendicitis.